PENGARUH PERLAKUAN PANAS NORMALIZING TERHADAP KEKUATAN TARIK PADA BAJA TULANGAN DEFORM PASCA KEBAKARAN - Prialdo, Rayel; Widagdo, Tri; Witjahjo, Soegeng (MACHINERY Jurnal Teknologi Terapan, 2021)
The purpose of this study was to determine the effect of normalizing treatment on tensile strength, yield stress and strain of reinforcing steel after fire. Normalizing treatment was carried out at a temperature of 800 ° C with a holding time of 25 minutes and compared the results of post fire reinforcing steel with after normalizing treatment. The goals of the normalizing process vary widely. Normalizing can increase or decrease the strength and hardness of steel, depending on the heat treatment and mechanical properties of the steel prior to the normalizing process. But in general the purpose of the normalizing process is to increase the machinability, grain-structure refinement, homogenization, and regulate or modify the residual stress that exists in steel. From the results of the tensile test after normalizing, the highest tensile strength value was obtained in the specimens cooled with water at 600 ° C at 597.85 N / mm² and the lowest value at 400 ° C with air at 443.9 N / mm². The largest yield stress value was at 600 ° C with water at 416.28 N / mm² and the lowest value at 800 ° C with air at 318.243 N / mm². The greatest value of strain was at 800 ° C with water at 31.66% and the smallest strain at 400 ° C with air at 21.67%.